Revisiting the Concept of al-Māl in the Digital Age: Theoretical and Practical Implications of CBDC Implementation in Islamic Economics - Adjeng Nurussalam; Rianto Anugerah Wicaksono (Journal of Digital Economic Studies, 2026)
Digital transformation in the global financial system presents an ontological tension between algorithmic technological innovation and the rigid principles of Islamic law. This article investigates the position of Central Bank Digital Currency (CBDC) or Digital Rupiah from a sharia economics perspective, highlighting the compatibility of its technical design with the doctrines of fiqh muamalah and maqās}id al-sharī‘ah. Using a qualitative approach based on literature studies and content analysis of Bank Indonesia policy documents and DSN-MUI fatwas, this study finds that the Digital Rupiah meets the criteria of legitimate property (al-māl) because it has legal intrinsic value and is guaranteed by state authority. Further analysis reveals that the Distributed Ledger Technology (DLT) architecture of the Digital Rupiah is capable of mitigating the risks of riba, gharar, and maysir through systemic transparency, while enhancing asset protection (hifz} al-māl) and promoting financial inclusion. This study recommends the formulation of a hybrid policy that integrates central bank technology standards with sharia compliance parameters to ensure ethical monetary sovereignty. In conclusion, the Digital Rupiah represents a harmonious synthesis of modernity and tradition, offering a new model of monetary architecture that is fair, efficient, and based on divine values.